Analysis of the Implementation of Character Education Based on Local Culture in Indonesia - Nasaruddin Nasaruddin; Ikhsan Maulana; Moh. Safrudin (STAI Hubbulwathan Duri, 2024)
This study aimed to evaluate the implementation of local culture-based character education in junior high schools across Bima City, NTB. Employing a cross-sectional survey design, the research focused specifically on SMPN 5 Bima City and SMPN 1 Bima City, involving 50 students and 50 teachers. Data were collected using questionnaires and documentation methods, resulting in the creation of two validated and reliable questionnaires, with reliability coefficients of 0.953 for the teacher questionnaire and 0.919 for the student questionnaire. The findings provide insights into the application of character education, revealing that the levels of honesty, discipline, responsibility, courtesy, and cooperation among teachers and students are generally moderate. The study also highlights how local cultural elements, such as Santabe Culture (politeness), Maja Labo Dahu Culture (modesty and caution), Nggahi Rawi Pahu Culture (integrity), and Su'u sa wau tundu sa wale Culture (responsibility), can be effectively integrated into character education frameworks at these schools.